Planned unparenthood creating a life without procreating - Alexander, Dann (Frogsong Productions, 2015)
"Planned UnParenthood is a refreshing look at life without having children. It gives a voice to those without children who may be afraid to say what they really want to say. It gives validity and understanding to those who are always explaining why they have made this lifestyle choice. It also gives parents some insight and thought into the attitudes they may have towards their friends and family who live life as non-parents. It looks at the differences between childfree and childless, while promoting adoption as a positive option for those who cannot have kids. It takes a hard look at the reality of a society that rewards parents automatically, while sometimes by default punishing those without children. This book will explain why creating life does not necessarily have to be the main purpose of living. It affirms that not having children is in fact an option, and is a choice worthy of respect."